2001
DOI: 10.1002/etc.5620200522
|View full text |Cite
|
Sign up to set email alerts
|

Phototactic behavior of Daphnia and the continuous monitoring of water quality: Interference of fish kairomones and food quality

Abstract: We carried out a laboratory study to evaluate the sensitivity of phototactic behavior of Daphnia magna to sublethal concentrations of pentachlorophenol (PCP) and copper. More specifically, we determined whether the sensitivity of a D. magna clone to those pollutants is influenced by food quality and the presence of fish kairomones. Test animals were fed either unicellular green algae (Scenedesmus acutus) or fresh baker's yeast (Saccharomyces cerevisiae) and were cultured in the presence or absence of fish kair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The lack of vertical migration by all isolates suggests that even at low levels metals are interfering with Daphnia’s response to fish kairomone cues. Similar findings have been shown in other studies examining invertebrate predator kairomone and their influence on Daphnia neonate neckteeth development in the presents of these same metals (Hunter and Pyle, 2004; Mirza and Pyle, 2009), and fish kairomone influence on photo-tactic behavior of Daphnia in the present of Cu (Dang Kieu et al, 2001; Yuan et al, 2003). While our study confirms earlier findings about copper it adds nickel to the list of metals that at low concentrations inhibits Daphnia’s responds to predatory fish cues.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of vertical migration by all isolates suggests that even at low levels metals are interfering with Daphnia’s response to fish kairomone cues. Similar findings have been shown in other studies examining invertebrate predator kairomone and their influence on Daphnia neonate neckteeth development in the presents of these same metals (Hunter and Pyle, 2004; Mirza and Pyle, 2009), and fish kairomone influence on photo-tactic behavior of Daphnia in the present of Cu (Dang Kieu et al, 2001; Yuan et al, 2003). While our study confirms earlier findings about copper it adds nickel to the list of metals that at low concentrations inhibits Daphnia’s responds to predatory fish cues.…”
Section: Discussionsupporting
confidence: 87%
“…Other results showed that cadmium decreased the velocity of Daphnia magna [24]. In the absence of pollutants, a clone (Daphnia magna) showed positively phototactic behavior, and the behavior became significantly less positive with increasing concentrations of a chemical substance [25]. In our opinion, the behavior of animals ensures ecological reactivity and adaptation to their (e.g.…”
mentioning
confidence: 51%
“…food abundance and quality, and the presence/absence of fish kairomones (e.g. Michels and De Meester, 1998;Cousyn et al, 2001;Kieu et al, 2001). Phototactic behavior in daphnids is also influenced by a variety of environmental pollutants (Michels et al, 2000;Semsari and Megateli, 2007;Brausch et al, 2011) and, given its relative ease to observe and quantify (Dojmi and Rotondo, 1988), has been used to monitor for these chemicals (e.g.…”
Section: Introductionmentioning
confidence: 99%